UTILIZATION, GROWTH, AND POPULATION OF BULLET TUNA (AUXIS ROCHEI RISSO 1810) IN INDIAN OCEAN SOUTHERN SUMBAWA - Asrial, Evron (Fakultas Perikanan Universitas 45 Mataram, 2020)
Bullet tuna (Auxis rochei Risso 1810) as an export commodity, have a positive impact on Indonesia's foreign exchange. Utilization status is fully exploited, and captured gonad immature. The aim of this study is to estimate the utilization, growth, and population of bullet tuna. Conducted in Labangka (Sumbawa Regency) during May-August 2019. The compilation of the fork length frequency data (FL) of bullet tuna uses sampling, observation, dialogue and documentation techniques. Alleged utilization level of bullet tuna resources is calculated using a surplus production model. Growth parameters (K and L?) were estimated by the Electronic Length Frequency Analysis (ELEFAN I) method on the Scanning of K-values FAO-ICLARM Stock Assessment Tools II (FiSAT II). FiSAT II software is also used for population estimation based on FL frequency data. Tuna fishing in Labangka uses surface longlines and outboard motorboats. The status of the utilization of bullet tuna in the waters of southern Sumbawa reaches fully exploited and low growth rates. Bullet tuna fisheries activities in Labangka are small scale fisheries that apply the rules of responsible fisheries. So that management is sustainable, it can be done by increasing the size of the fishing line, beginning with the socialization to fishermen.